1986
DOI: 10.1111/j.1745-6606.1986.tb00369.x
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Response to Adjustable Rate Mortgages: Implications of the Evidence from Illinois and Wisconsin

Abstract: The innovation-adoption framework is used to determine consumers' levels of awareness of AMIs and the degrees to which they are able and willing to evaluate andlor accept the complicated alternatives available to them. A mail survey of consumers in Illinois and Wisconsin was structured to compare previous studies on this topic and to compare consumers across various demographic categories. Results indicate that awareness of AMIs is increasing, as is the willingness to accept them with an initial interest rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…These stages emanate from the first phases of our research (in-depth interviews and group discussions) and from the paradigm derived from the research of Booz, Allen and Hamilton (1982). Support for this construct can also be found in the product development literature (Bowers, 1986;Cooper, 1986;Crawford, 1987;Mills and Gardner, 1986;Nevers, 1972). We conclude from all these sources that information about the customer is essential for development, screening and market launch planning of a new service innovation and is in keeping with the essence of the marketing concept.…”
Section: Findings: Objectivementioning
confidence: 81%
“…These stages emanate from the first phases of our research (in-depth interviews and group discussions) and from the paradigm derived from the research of Booz, Allen and Hamilton (1982). Support for this construct can also be found in the product development literature (Bowers, 1986;Cooper, 1986;Crawford, 1987;Mills and Gardner, 1986;Nevers, 1972). We conclude from all these sources that information about the customer is essential for development, screening and market launch planning of a new service innovation and is in keeping with the essence of the marketing concept.…”
Section: Findings: Objectivementioning
confidence: 81%
“…Data were collected from 158 students in an MBA program. MBA students were selected partly for the same reasons Mills and Gardner (1986) selected them -their knowledge level about mortgages was expected to be reasonably high, and so they would be able to meaningfully make the choices required by the survey. Four of the responses were deleted from the study due to incompleteness.…”
Section: Resultsmentioning
confidence: 99%
“…The 1980-82 drainage of funds from the mortgage-lending thrift-institutions resulted in the recognition of the need to encourage a widespread usage and acceptance of alternative mortgage instruments (AMIs) and to distinguish them from the historically well known FRMs. These new mortgage instruments shifted the risk of fluctuating interest rates (hence fluctuating costs of funds) from the lender to the borrower (Mills and Gardner, 1986). On the one hand these instruments allowed the lenders to achieve portfolio flexibility.…”
mentioning
confidence: 99%
“…A study by Mills and Gardner from 1986 showed that the majority of the customers preferred more riskless fixed rate mortgages than the ARM (Mills & Gardner, 1986). In 2008, Bucks and Pence also described the adjustable rate mortgages, especially the part of the subprime adjustable rate mortgages, as more complicated than fixed rate mortgages (Bucks & Pence, 2008).…”
Section: Types Of Mortgagesmentioning
confidence: 99%